Cooperation between Ulama and Umara through the Formation of Noble Morals for the Deli Serdang Community in Creating Community Security Stability - Fitria Ningsih; Widya Kartika; Nurul Aulia Ersa Putri; Naisha Faradilla; Nurul Khoiria; Said Fahrezi; Khairul Aula Siregar; Satria Andy (Maklumat: Journal of Da'wah and Islamic Studies, 2025)
Security stability is a key factor in creating a prosperous society. In Islam, this security stability can be achieved through cooperation between the Ulama (Islamic scholars) and the Umara (Islamic leaders). The Ulama act as transmitters of religious teachings, bringing messages of peace and togetherness, while the Umara are responsible for implementing policies that ensure the welfare of society. This study examines the roles of the Ulama (Islamic scholars) and the Umara (Islamic leaders) in maintaining security stability and how synergy between the two can create a harmonious and prosperous society.